2022
DOI: 10.4236/gep.2022.108014
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Distribution Coefficient (<i>K<sub>d</sub></i>) of Some Selected Heavy Metals over the Last Decade (2012-2021)

Abstract: This review synthesizes the methods for estimating the distribution coefficient (K d ) and provides a compilation of K d values for five heavy metals (As, Pb, Cd, Cu, and Zn) based on research published in the last decade (2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021). We used the PRISMA method to ensure the transparency of the collected data. For mono-metal systems (MS), the K d values ranged from 10 −2 to 10 7 L/kg for Pb, from 10 −2 to 10 6 L/kg for Cd, As, and Zn, and from 10 −2 to 10 5 L/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 109 publications
(128 reference statements)
1
1
0
Order By: Relevance
“…These positive correlations obtained from the relationships could be due to the formation of complexes (inner and outer) by the heavy metals with organic components in the soil largely due to the chelating effects of its functional groups. The result obtained in this study is consistent with the reports of Elbana et al (2018) and Seidou et al (2022), which found that organic matter in soils showed strong sorption with heavy metals. The R value (0.68) obtained also largely reflected the quantity of organic matter content in the study soil, which was low, as shown in Table 1.…”
Section: Adsorption Studiessupporting
confidence: 93%
“…These positive correlations obtained from the relationships could be due to the formation of complexes (inner and outer) by the heavy metals with organic components in the soil largely due to the chelating effects of its functional groups. The result obtained in this study is consistent with the reports of Elbana et al (2018) and Seidou et al (2022), which found that organic matter in soils showed strong sorption with heavy metals. The R value (0.68) obtained also largely reflected the quantity of organic matter content in the study soil, which was low, as shown in Table 1.…”
Section: Adsorption Studiessupporting
confidence: 93%
“…They influence the kinetics of sorption-desorption reactions, the metal concentration in the extraction solution, and the form of soluble or insoluble chemical species [11]. The assessment and prediction of toxic metals in soil requires knowledge of their distribution in the solid-liquid system, expressed by the distribution coefficient Kd [12][13][14][15]. The Kd value of metal indicates the effect of various reactions in the solid and liquid phases.…”
Section: Introductionmentioning
confidence: 99%